PENGEMBANGAN MEDIA PERMAINAN LUDO PEMBAGIAN ANGKA (PELUPA) PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN LITERASI MATEMATIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Utami, Diah Ayu; Kusuma, Dani (Universitas Negeri Medan, 2024)
This research aims to produce media in the form of a ludo game for dividing numbers using porogapit multilevel division material that is effective, valid, effective and practical. This type of research is development research or can be called Research and Development (R&D) using the ADDIE stage model. The subjects of this research consisted of 18 class IV students at SD Negeri Mangunsari 01 Salatiga. The effectiveness trial was carried out by giving a pretest and posttest to students, then the results obtained were carried out by a t-test using SPSS Statistics 25. From the t-test results of the initial measurement and final measurement, the Sig value was obtained. (2-tailed) of 0.000. These results show that the Sig value. (2-tailed) < 0.05, then Ho is rejected and Ha is accepted, meaning that there is an influence in the use of the ludo game media for dividing numbers which can be said to be effective. The effectiveness trial was carried out by giving a pretest and posttest to students, then the results obtained were carried out by a t-test using SPSS Statistics 25. From the t-test results of the initial measurement and final measurement, the Sig value was obtained. (2-tailed) of 0.000. These results show that the Sig value. (2-tailed) < 0.05, then Ho is rejected and Ha is accepted, meaning that there is an influence in the use of the ludo game media for dividing numbers which can be said to be effective.